PENGUATAN LITERASI REFERENSI DIGITAL MAHASISWA UNIVERSITAS ROKANIA MELALUI PELATIHAN APLIKASI MENDELEY - Sri Wahyudi; Detri Amelia Chandra; Agung Setiawan; Fauzi Erwis; Jufri Jufri; Safrudin Safrudin (Smart Education, 2025)
Abstract: Enhancing digital reference literacy has become an urgent necessity in the modern academic era. This study aims to analyze the effectiveness of Mendeley application training in improving the ability of Rokania University students to manage digital references and produce scientific citations. A descriptive qualitative approach was employed through observation, interviews, and documentation. The results show that the training improved students’ competencies in importing references, managing metadata, using the Web Importer, and automating bibliographies. The implementation of the Mendeley application increased the efficiency of scientific writing and minimized citation errors commonly found in student academic work. This study affirms that digital reference literacy must become an integral component of academic competency development in higher education. Keyword: digital literacy, mendeley, citation, scientific references, students. Abstrak: Peningkatan literasi referensi digital merupakan kebutuhan mendesak pada era akademik modern. Penelitian ini bertujuan menganalisis efektivitas pelatihan aplikasi Mendeley dalam meningkatkan kemampuan mahasiswa Universitas Rokania dalam mengelola referensi digital dan menyusun sitasi ilmiah. Pendekatan deskriptif kualitatif digunakan melalui observasi, wawancara, dan dokumentasi. Hasil menunjukkan bahwa pelatihan ini meningkatkan kompetensi mahasiswa dalam impor referensi, pengelolaan metadata, penggunaan Web Importer, hingga otomatisasi daftar pustaka. Penerapan aplikasi Mendeley meningkatkan efisiensi penulisan ilmiah dan meminimalisasi kesalahan sitasi yang sering terjadi dalam karya ilmiah mahasiswa. Penelitian ini menegaskan bahwa literasi referensi digital perlu menjadi bagian integral dari pengembangan kompetensi akademik di perguruan tinggi. Kata kunci: literasi digital, mendeley, sitasi, referensi ilmiah, mahasiswa